2015
DOI: 10.1128/ec.00287-14
|View full text |Cite
|
Sign up to set email alerts
|

Yeast β-1,6-Glucan Is a Primary Target for the Saccharomyces cerevisiae K2 Toxin

Abstract: b Certain Saccharomyces cerevisiae strains secrete different killer proteins of double-stranded-RNA origin. These proteins confer a growth advantage to their host by increasing its survival. K2 toxin affects the target cell by binding to the cell surface, disrupting the plasma membrane integrity, and inducing ion leakage. In this study, we determined that K2 toxin saturates the yeast cell surface receptors in 10 min. The apparent amount of K2 toxin, bound to a single cell of wild type yeast under saturating co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 31 publications
2
26
0
1
Order By: Relevance
“…The analysis showed that as long as the saturation of the receptors on the cell wall was avoided, the binding kinetics remained constant (Fig, 1b). Similar binding rates were reported in experiments where the initial unbound toxin concentration was varied by more than 50-fold, providing further support for these findings [25,27].…”
Section: Molecular Crowding Around Cell Wall Receptors Impedes Bindinsupporting
confidence: 85%
See 2 more Smart Citations
“…The analysis showed that as long as the saturation of the receptors on the cell wall was avoided, the binding kinetics remained constant (Fig, 1b). Similar binding rates were reported in experiments where the initial unbound toxin concentration was varied by more than 50-fold, providing further support for these findings [25,27].…”
Section: Molecular Crowding Around Cell Wall Receptors Impedes Bindinsupporting
confidence: 85%
“…K1 molecules/cell was proposed[27]. The number of β -1,6-D-glucans on a haploid parent yeast cell wall was estimated to vary in the range of 6,600,000 to 11,000,000[26,53], and would be even higher for diploid cells than these reported here.…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…Hydrolysis and fractionation techniques used routinely to determine the polysaccharide content of the sugar of interest have demonstrated that not even trace amounts of di-, tri-, or tetrasaccharides are observed in pustulan, indicating that the molecule is linear in nature and contains exclusive ␤-1,6 glucan linkages (21). Other researchers have routinely used pustulan to study ␤-1,6 glucan-C-type lectin receptor (CLR) interactions and yeast ␤-1,6 glucan cell wall biology (22)(23)(24)(25)(26).…”
Section: Methodsmentioning
confidence: 99%
“…Cells that are susceptible to these toxins were identified to possess two different types of sites or receptors that bind the killer toxin with different affinities [26]. The first step of K1/K2 binding was reported as the low affinity, high velocity, energy independent adsorption of the killer toxin on b-1,6-D-glucans embedded in the cell wall [27,28]. Once bound, the toxin had a high affinity, low velocity, energydependent interaction with Kre1p receptors, which are glycosyl-phosphatidylinositol-linked glycoproteins located on the cell membrane [29,30].…”
Section: Introductionmentioning
confidence: 99%